Type 2 Diabetes Mellitus and COVID-19: A Narrative Review - Corrao, Salvatore; Pinelli, Karen; Vacca, Martina; Raspanti, Massimo; Argano, Christiano (Frontiers in Endocrinology, 2021)
The pandemic of coronavirus disease (COVID-19), a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has involved more than thirty million individuals, including more than nine hundred thousand deaths. Diabetes represents one of the most prevalent chronic conditions worldwide and significantly increases the risk for hospitalization and death in COVID-19 patients. In this review, we discuss the prevalence, the pathophysiological mechanisms, and the outcomes of COVID-19 infection in people with diabetes. We propose a rationale for the use of drugs prescribed in patients with diabetes and some pragmatic clinical recommendations to deal with COVID-19 in this kind of patients.